(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
The study aims to know the profile of the respondents in terms of age, gender, educational attainment, and monthly family average income of parents and to identify how the support is extended by the parents on their special need children toward their studies along the area of becoming a strong advocate, getting acquainted with school regulation, learning to access additional services, developing relationship with children module tutors, and future of special need children. The descriptive quantitative research design is employed in the study. The subjects of the study are the parents of the special needs children who are enrolled in the different Higher Education Institutions (HEI) both in private and government entities in the GCC country. Twenty (20) parents are topped in the utilization of the study. A non-probability sampling technique is utilized in the study which is purposive sampling because it is appropriate in the development of the study. The results show that there is no significant relationship between the profile of the respondents and how support is extended by the parents of the special need children toward their studies